If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1y) * dx + -1(2x) * dy = 0 Reorder the terms for easier multiplication: dx(x + -1y) + -1(2x) * dy = 0 (x * dx + -1y * dx) + -1(2x) * dy = 0 Reorder the terms: (-1dxy + dx2) + -1(2x) * dy = 0 (-1dxy + dx2) + -1(2x) * dy = 0 Remove parenthesis around (2x) -1dxy + dx2 + -1 * 2x * dy = 0 Multiply -1 * 2 -1dxy + dx2 + -2x * dy = 0 Multiply x * dy -1dxy + dx2 + -2dxy = 0 Reorder the terms: -1dxy + -2dxy + dx2 = 0 Combine like terms: -1dxy + -2dxy = -3dxy -3dxy + dx2 = 0 Solving -3dxy + dx2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'dx'. dx(-3y + x) = 0Subproblem 1
Set the factor 'dx' equal to zero and attempt to solve: Simplifying dx = 0 Solving dx = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-3y + x)' equal to zero and attempt to solve: Simplifying -3y + x = 0 Reorder the terms: x + -3y = 0 Solving x + -3y = 0 Move all terms containing d to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + -3y = 0 + -1x Combine like terms: x + -1x = 0 0 + -3y = 0 + -1x -3y = 0 + -1x Remove the zero: -3y = -1x Add '3y' to each side of the equation. -3y + 3y = -1x + 3y Combine like terms: -3y + 3y = 0 0 = -1x + 3y Simplifying 0 = -1x + 3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -2x^2(-5x^2+4x^3)= | | -4x^2-32x+17=0 | | 78x=92 | | -13=-1+-6x | | (19)+(13)= | | 5x-6=33 | | 5(x+2)+5=5x+2 | | -11a-9+4a= | | 92=78x | | (x-y)dx+2xdy=0 | | 4.19=p-6.3 | | -9x^3+111x^2+78x=0 | | 17x+6y=3x^2 | | (23)+(-19)= | | s/10=7 | | (23)+(19)= | | 15x*12y=13 | | 15xy= | | -4p+6-10q+4p+3= | | 4x+13-6x=15-18x+16x-2 | | (-24)-(-5)= | | -4=-3-x/1 | | 6g^3-24g^2+24g=0 | | 4x+13-6x=15-18x+16-2 | | 10=2*3+2w | | (-4t^2)^2/2t | | 10+3x=2(3+4c)+5 | | 7-14y-18+9y= | | (1-y)dx-(1-x)dy=0 | | 80z^8-46z^6=0 | | 3(2x-3)-1=6x-10 | | 52=x+(2x-5) |